2008
DOI: 10.1088/1126-6708/2008/07/030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical threshold enhancement and resummation in Drell-Yan production

Abstract: Partonic cross sections for the production of massive objects in hadronic collisions receive large corrections when the invariant mass of the initial-state partons is just above the production threshold. Since typically the center-of-mass energy of the hadronic collision is much higher than the mass of the heavy objects, it is not obvious that these contributions translate into large corrections to the hadronic cross section. Using a recent approach to threshold resummation based on effective field theory, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
527
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 241 publications
(542 citation statements)
references
References 75 publications
(196 reference statements)
15
527
0
Order By: Relevance
“…To analytically continue the result to negative η values, or to improve convergence, it is useful to perform subtractions [30,32]. A single subtraction would use…”
Section: Subtractionsmentioning
confidence: 99%
See 3 more Smart Citations
“…To analytically continue the result to negative η values, or to improve convergence, it is useful to perform subtractions [30,32]. A single subtraction would use…”
Section: Subtractionsmentioning
confidence: 99%
“…For electroweak boson production at large transverse momentum, they amount to 70-80% of the NLO correction [19]. For inclusive Drell-Yan and Higgs production, also the NNLO correction is known, and it is found that a similarly large fraction of the perturbative corrections arises from the partonic threshold region [30,40].…”
Section: Scale Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Since observables at the LHC generally involve many scales, it is likely that resummation will lead to a quantitatively significant improvement of our theoretical predictions. Recent advances in Soft-Collinear Effective Theory have shown resummation to be achievable at the next-to-leading (NLL) [1,2], next-to-nextto-leading (NNLL) [3,4,5,6] and next-to-next-to-next-to-leading (N 3 LL) logarithmic order [7,8,9,10,11,12,13]. Practical results have included a precise measurement of α s from event shapes [10,11], better agreement with Tevatron data and reduced theoretical uncertainty for the the direct photon p T spectrum [5], and a bound on possible new colored states [14].…”
mentioning
confidence: 99%